2020
DOI: 10.1111/cico.12445
|View full text |Cite
|
Sign up to set email alerts
|

“Because the World Consists of Everybody”: Understanding Parents’ Preferences for Neighborhood Diversity

Abstract: Previous research, primarily using survey data, highlights preferences about neighborhood racial composition as a potential contributor to residential segregation. However, we know little about how individuals, especially parents, understand neighborhood racial composition. We examine this question using in‐depth interview data from a racially diverse sample of 156 parents of young children in two metropolitan areas. Prior scholarship on neighborhood racial preferences has mostly been animated by expectations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Such neighborhoods may even be in short supply in some places. Darrah-Okike et al (2020) reported that the realization of living in a socially and racially integrated neighborhood environment was stymied by the lack of availability of such places, a predicament made more acute for the economically disadvantaged.…”
Section: Unbufferingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such neighborhoods may even be in short supply in some places. Darrah-Okike et al (2020) reported that the realization of living in a socially and racially integrated neighborhood environment was stymied by the lack of availability of such places, a predicament made more acute for the economically disadvantaged.…”
Section: Unbufferingmentioning
confidence: 99%
“…Darrah–Okike et al. (2020) offer a counterpoint. Their research, which drew on in‐depth interviews with parents of young children in Houston and Cleveland, found that a significant share wanted to live in racially mixed neighborhoods.…”
Section: Introductionmentioning
confidence: 99%
“…Whites in these studies express concern about the economic wisdom of purchasing a home in a black or multiracial neighborhood where property values are perceived as being less stable and schools less academically rigorous than those in white neighborhoods (Johnson and Shapiro 2003;Krysan 2002b;Krysan et al 2009). Despite the fact that white neighborhoods remain the norm for the majority of white Americans, there is growing evidence that a subset of middle to upper-class white individuals are becoming increasingly more open to establishing residence in a racially diverse neighborhood (Burke 2012;Darrah-Okike et al 2020;Fischer and Lowe 2015;Iceland and Sharp 2013;Maly 2011;Mayorga-Gallo 2014;Rich 2011;Underhill 2019). This is especially true of first-time homebuyers who are either childless or whose children are not yet elementary school age (Fischer and Lowe 2015;Goyette et al 2014).…”
Section: Residential Attitudes Trends and Behaviors Of White Americansmentioning
confidence: 99%
“…This article is, to the best of my knowledge, the first to investigate how white, middle-class parents think about the poor residents who live in their mixed-income neighborhood and, more importantly, what they do to manage their children’s exposure to the poor. While research examines white people’s attitudes about “diversity” and, to a lesser extent, their desire or reluctance to live in a racially diverse neighborhood (Bobo and Zubrinsky 1996; Burke 2012; Darrah-Okike, Harvey and Fong 2020; Mayorga-Gallo 2014), little is known about the practices parents deploy in economically and racially diverse settings. This article makes empirical contributions to research on neighborhood social processes concerning the role white, middle-class parents play in creating and sustaining neighborhood-level micro-segregation in two racially distinct mixed-income neighborhoods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation